Impact of iatrogenic alterations on adjacent segment degeneration after lumbar fusion surgery: a systematic review - Moritz Jokeit; Christos Tsagkaris; Franziska C. S. Altorfer; Frédéric Cornaz; Jess G. Snedeker; Mazda Farshad; Jonas Widmer (Journal of Orthopaedic Surgery and Research)
Abstract Purpose Adjacent segment degeneration (ASDeg) and disease (ASDis) remain significant challenges following lumbar spinal fusion surgery, with reported incidences of 36% for ASDeg and 11% for ASDis within two to seven years post-operation. However, the mechanisms leading to the development of ASDeg are still poorly understood. This comprehensive review aims to elucidate the multifactorial etiology of ASDeg by examining important iatrogenic alterations associated with spinal fusion. Methods A systematic review following PRISMA guidelines was conducted to identify clinical studies quantifying the occurrence of ASDeg and ASDis after lumbar fusion surgery. An EMBASE and citation search up to April 2023 yielded 378 articles. Data extracted encompassed study design, fusion type, sample size, patient age, and incidence of ASDeg and ASDis. A total of 87 publications were analyzed in the context of iatrogenic alterations caused by surgical access (muscle damage, ligament damage, facet joint damage) and instrumentation (fusion angle, immobilization). Results Ligament damage emerged as the most impactful iatrogenic factor promoting ASDeg and ASDis development. Similarly, muscle damage had a significant impact on long-term musculoskeletal health, with muscle-sparing approaches potentially reducing ASDis rates. Immobilization led to compensatory increased motion at adjacent segments; however, the causal link to degeneration remains inconclusive. Fusion angle showed low evidence for a strong impact due to inconsistent findings across studies. Facet joint violations were likely contributing factors but not primary initiators of ASDeg. Conclusion Based on the analyzed literature, ligament and muscle damage are the most impactful iatrogenic factors contributing to ASDeg and ASDis development. Minimally invasive techniques, careful retractor placement, and ligament-preserving decompression may help mitigate these effects by reducing undue muscle and ligament trauma. Although it is not possible to definitively advocate for one or more techniques, the principle of selecting the most tissue-sparing approach needs to be scaled across surgical planning and execution. Further research is necessary to fully elucidate these mechanisms and inform surgical practices to mitigate ASDeg risk.